The Influence of Play Activities, Nutritional Status and Motor Ability on The Physical Fitness of Primary School Students - Putra, Riwaldi; Putra, Deri; Nanda, Fitri Agung (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This research aims to reveal the influence of playing activities, nutritional status and motor skills on physical fitness. This research method is quantitative using a path analysis approach. The population of this study was all students at SD N 14 Jati Tanah Tinggi, Padang City, totaling 163 people. The sampling technique was carried out by purposive sampling, with a total sample of 49 people. Data was collected by filling out questionnaires for playing activities, measuring body weight and height for nutritional status, throwing a basketball, running for four seconds, passing a ball against a wall and jumping without a start to measure motor skills, and to measure students' physical fitness, the TKJI test was used to elementary school age children. The results of research and data analysis show that: (1) Playing activities have a direct and significant effect on physical fitness by 12.6% (2) Nutritional status has a direct and significant effect on physical fitness by 12.4% ( 3) Motor Ability has a direct and significant effect on physical fitness by 9.2% (4) Playing activities have an indirect effect on Physical Fitness through Motor Ability by 17.7% (5) Nutritional status has an indirect effect on Physical Fitness through Motor Ability is 28.1% (6) Playing Activities, Nutritional Status and Motor Ability simultaneously influence students' Physical Fitness by 48.2%